2014
DOI: 10.1002/ange.201309464
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Backfilling Mitigates the Negative Impact of the Protein Corona on Nanoparticle Cell Targeting

Abstract: Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the TSpace version (original manuscript or accepted manuscript) because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 34 publications
(17 reference statements)
1
49
0
Order By: Relevance
“…In contrast, addition of the cDNA strand increases the DNA density, resulting in improved protection. Another important factor is the effect of PEG backfill layer, which blocks enzymatic access to DNA (17,(24)(25)(26)(27). DNA strand that is shorter than the thickness of the PEG layer is protected from protein binding by being fully submersed within the PEG molecules.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, addition of the cDNA strand increases the DNA density, resulting in improved protection. Another important factor is the effect of PEG backfill layer, which blocks enzymatic access to DNA (17,(24)(25)(26)(27). DNA strand that is shorter than the thickness of the PEG layer is protected from protein binding by being fully submersed within the PEG molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the in vivo antitumor efficacy of ATB was markedly enhanced without significant toxicity in normal tissues. Previous studies have reported that the affinity of nanocarriers for cells or organs may attribute to their interaction with cell membranes [30][31][32][33][34] . Moreover, this effect is conducive for ATB to play a strong tumor curative effect in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan reportedly exhibits exceptional adhesion ability with lung cancer cells through H-bonding interaction and biotic stickiness [23][24][25][26] . In addition, Pluronic copolymers, which have a hydrophilic and flexible nature similar to PEG [27][28][29] , are often used to prevent the adsorption of plasma protein, resulting in increased accumulation at the tumor site [30][31][32][33][34] . Thus, we sought to exploit and combine the biotic stickiness of chitosan and the enhanced accumulation effect of PEGylation to generate polymer micelles to promote the affinity and cellular uptake of ATB toward lung tumor cells.…”
Section: Original Articlementioning
confidence: 99%
“…Surface passivation reduces both macrophage uptake and increases blood circulation half-life for a variety of nanoparticle types [43][44][45]. In addition, the loss of specificity due to serum protein adsorption and nanoparticle aggregation is also drastically reduced with appropriate passivation of the surface with PEG [37,46]. However, proteins continue to adsorb on the nanoparticle surface even when the nanoparticle surface is decorated with a very dense layer of PEG [43].…”
Section: Surface Passivation Is the Predominant Strategy To Reduce Thmentioning
confidence: 95%